2021
DOI: 10.1371/journal.pone.0258481
|View full text |Cite
|
Sign up to set email alerts
|

Sub pixel resolution using spectral-spatial encoding in x-ray imaging

Abstract: Purpose Previous efforts at increasing spatial resolution have relied on decreasing focal spot and or detector element size. Many “super resolution” methods require physical movement of a component of the imaging system. This work describes a method for achieving spatial resolution on a scale smaller than the detector pixel without motion of the object or detector. Methods We introduce a weighting of the photon energy spectrum on a length scale smaller than a single pixel using a physical filter that can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Li et al suggested to move the rotation stage in a fixed trajectory during the data acquisition to obtain multiple projection images with sub-pixel displacements 14 . Szczykutowicz et al developed a spectral-spatial encoding method that acquires multiple measurements at different beam energies and different spatial positions to decompose the line integrals into two unique bases 15 . However, one major limitation of these studies is the prolonged data acquisition period due to the repeated measurements.…”
Section: A Super Resolution Ct Imaging Methodsmentioning
confidence: 99%
“…Li et al suggested to move the rotation stage in a fixed trajectory during the data acquisition to obtain multiple projection images with sub-pixel displacements 14 . Szczykutowicz et al developed a spectral-spatial encoding method that acquires multiple measurements at different beam energies and different spatial positions to decompose the line integrals into two unique bases 15 . However, one major limitation of these studies is the prolonged data acquisition period due to the repeated measurements.…”
Section: A Super Resolution Ct Imaging Methodsmentioning
confidence: 99%
“…For these reasons, many recent studies focus on no-reference full-resolution quality indexes [76,78,80,82]. It is also worth recalling that the assessment of spectral and spatial consistencies is not necessarily linked to a fusion task and is of broader interest, with applications in the medical [84], agricultural [85], and food [86] sciences, to mention a few.…”
Section: Reduced-resolution Assessmentmentioning
confidence: 99%